Basic principles of shariah: UiTM law foundation student’s attitude and perceptions / Norazmi Anas, Ahmad Fadhir Mat Dahan and Zuriani Yaacob - Anas, Norazmi; Mat Dahan, Ahmad Fadhir; Yaacob, Zuriani (Universiti Teknologi MARA, Perlis, 2016)
Islam implies the complete submission and implementation of the commandments of Allah (swt). For that reason, Islamic law or shariah is essential for the maintenance of civilised life of Muslim community irrespective of race, nationality, creed and colour. Not only that, shariah law which comprises of several branches i.e. morals, worship, beliefs, contracts and punishments is governed to develop a society in which equity and justice are secured for every individual. In order to spread the ideals and values of Islamic jurisprudence, education should be a process that is infused with meaning and purpose in which later every individual will gain deeply held beliefs. On that note, the fundamental aim and objective of Basic Principles of Shariah embedded in the syllabus at UiTM is to establish and promote Muslim individuals who take interests in religious commands and prohibitions. In fact, the course is offered in the second semester of the programme and delivered according to specific objectives in an age-appropriate manner. This is crucial in providing Muslim graduates with a holistic view of their faith and its practice. This study employed questionnaire in order to collect data from 230 Muslim students enrolled in the course of Basic Principles of Shariah. All these students were majoring in the Foundation Programme of Law at UiTM Pahang Kuantan Campus for the years of 2012 and 2013. The results found were mean value between 3.69 to 4.79 and mean value between 2.43 to 4.50 for each research objective and this suggested that the Basic Principles of Shariah has successfully expanded students’ knowledge about Islam and further encouraged the students’ implementation of religious values in life. The results obtained also proposed that the respondents agreed with the relevancy and flexibility of shariah in the light of changing social and cultural circumstances yet remaining faithful to the key tenets and central objectives underpinning shariah.